2016
DOI: 10.1159/000445582
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin-Induced Suicidal Erythrocyte Death

Abstract: Background/Aims: The novel antifungal drug Anidulafungin is used for the treatment of diverse fungal infections including candidiasis and aspergillosis. The traditional antifungal drug amphotericin B has previously been shown to trigger eryptosis, the suicidal death of erythrocytes characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface. Triggers of eryptosis include increase of cytosolic Ca2+ activity ([Ca2+]i Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Side effects of micafungin treatment are known to include microangiopathic hemolytic anemia and thrombocytopenia with microvascular thrombosis [ 5 ]. One possible mechanism of thrombosis development involves eryptosis, i.e., the suicidal death of erythrocytes characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface [ 5 ]. Peter et al showed that micafungin triggers hemolysis and eryptosis with cell shrinkage and phospholipid scrambling of the erythrocyte cell membrane [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Side effects of micafungin treatment are known to include microangiopathic hemolytic anemia and thrombocytopenia with microvascular thrombosis [ 5 ]. One possible mechanism of thrombosis development involves eryptosis, i.e., the suicidal death of erythrocytes characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface [ 5 ]. Peter et al showed that micafungin triggers hemolysis and eryptosis with cell shrinkage and phospholipid scrambling of the erythrocyte cell membrane [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism of thrombosis development involves eryptosis, i.e., the suicidal death of erythrocytes characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface [ 5 ]. Peter et al showed that micafungin triggers hemolysis and eryptosis with cell shrinkage and phospholipid scrambling of the erythrocyte cell membrane [ 5 ]. There is no evidence in the literature presenting similar behavior due to voriconazole intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocytes from newborns are highly sensitive to oxidative stress leading to rapid eryptosis and subsequent clearance of those erythrocytes following birth . Eryptosis is triggered by complement, hyperosmotic shock, energy depletion, oxidative stress, cellular K + loss, hyperthermia and a wide variety of xenobiotics including diverse cytostatic drugs (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Eryptosis is suppressed by AMP activated kinase AMPK [73], cGMP-dependent protein kinase [74], mitogen and stress activated kinase MSK1/2 [75], PAK2 kinase [76] and sorafenib/sunitinib sensitive kinases [77, 78]. Eryptosis is triggered by a wide variety of conditions including hyperosmotic shock [61], oxidative stress [61], energy depletion [61], or exposure to diverse xenobiotics [61, 79‒137]. Several clinical disorders are associated with enhanced eryptosis, such as iron deficiency [61], dehydration [138], hyperphosphatemia [139], chronic kidney disease (CKD) [140‒143], hemolytic-uremic syndrome [144], diabetes [145], hepatic failure [79], malignancy [146, 147], arteriitis [148], sepsis [149], sickle-cell disease [61], beta-thalassemia [61], Hb-C and G6PD-deficiency [61], Wilsons disease [149], as well as advanced age [150].…”
Section: Introductionmentioning
confidence: 99%